2016
DOI: 10.1002/cam4.682
|View full text |Cite
|
Sign up to set email alerts
|

History of chickenpox in glioma risk: a report from the glioma international case–control study (GICC)

Abstract: Varicella zoster virus (VZV) is a neurotropic α‐herpesvirus that causes chickenpox and establishes life‐long latency in the cranial nerve and dorsal root ganglia of the host. To date, VZV is the only virus consistently reported to have an inverse association with glioma. The Glioma International Case‐Control Study (GICC) is a large, multisite consortium with data on 4533 cases and 4171 controls collected across five countries. Here, we utilized the GICC data to confirm the previously reported associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
0
40
0
3
Order By: Relevance
“…Due to differences in infrastructure, resources, and institutional policies, different types of controls and questionnaire administration methods had to be used across sites. However, we conducted a series of sensitivity analyses [detailed in (34)] to ensure that control type or questionnaire administration method did not discernably bias the results presented here. Nonetheless, we are unsure why the site-specific OR from UCSF demonstrates a significant adverse association between respiratory allergies and glioma here, as previous UCSF studies have reported inverse associations similar to those observed at our other sites (11, 20, 42).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to differences in infrastructure, resources, and institutional policies, different types of controls and questionnaire administration methods had to be used across sites. However, we conducted a series of sensitivity analyses [detailed in (34)] to ensure that control type or questionnaire administration method did not discernably bias the results presented here. Nonetheless, we are unsure why the site-specific OR from UCSF demonstrates a significant adverse association between respiratory allergies and glioma here, as previous UCSF studies have reported inverse associations similar to those observed at our other sites (11, 20, 42).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the GICC study can be found elsewhere (34). Briefly, the GICC is an international consortium with 14 recruitment sites across five countries: Brigham and Women’s Hospital (MA, USA), Case Western Reserve University (Ohio, USA), Columbia University (NY, USA), Danish Cancer Society Research Centre (Copenhagen, Denmark), The Gertner Institute (Tel Hashomer, Israel), Duke University (NC, USA), University of Texas MD Anderson Cancer Center (TX, USA), Memorial Sloan Kettering Cancer Center (NY, USA), Mayo Clinic (MN, USA), NorthShore HealthSystem ( IL, USA), Umeå University (Umeå, Sweden), University of California, San Francisco (CA, USA), University of Southern California (CA, USA) and The Institute of Cancer Research (London, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations